GEOGRAPHIC INFORMATION SYSTEM BASED SUPPORT VECTOR MACHINE MODELING FOR SOIL EROSION SUSCEPTIBILITY MAPPING - SHOLAGBERU, ABDULKADIR TAOFEEQ (2018)
Soil erosion hazard has been recognized as one of the biggest environmental challenges. It becomes more problematic in human-altered mountainous watershed like Cameron Highlands. Literature survey revealed the issues of subjectivity in selecting erosion causative factors (CFs) for susceptibility modeling due to lack of specific guideline. To date, some crucial dynamic CFs are not considered and support vector machine (SVM) techniques are scarcely explored in the previous susceptibility mapping.